Responses of midgut amylases of Helicoverpa armigera to feeding on various host plants - Kotkar, Hemlata M.; Sarate, Priya J.; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Physiology, 2009)
Midgut digestive amylases and proteinases of Helicoverpa armigera, a polyphagous and devastating insect pest of economic importance have been studied. We also identified the potential of a sorghum amylase inhibitor against H. armigera midgut amylase. Amylase activities were detected in all the larval instars, pupae, moths and eggs; early instars had lower amylase levels which steadily increased up to the sixth larval instar. Qualitative and quantitative differences in midgut amylases of H. amigera upon feeding on natural and artificial diets were evident. Natural diets were categorized as one or more members of legumes, vegetables, flowers and cereals belonging to different plant families. Amylase activity and isoform patterns varied depending on host plant and/or artificial diet. Artificial diet-fed H. armigera larvae had comparatively high amylase activity and several unique amylase isoforms. Correlation of amylase and proteinase activities of H. armigera with the protein and carbohydrate content of various diets suggested that H. armigera regulates the levels of these digestive enzymes in response to macromolecular composition of the diet. These adjustments in the digestive enzymes of H. armigera may be to obtain better nourishment from the diet and avoid toxicity due to nutritional imbalance. H. armigera, a generalist feeder experiences a great degree of nutritional heterogeneity in its diet. An investigation of the differences in enzyme levels in response to macronutrient balance and imbalance highlight their importance in insect nutrition. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amylase inhibitors; Diet; Helicoverpa armigera larvae; Midgut amylase; Proteinases